Design and control of a bidirectional interlinking converter for grid energy for storage - Huang, Yiyuan (Nanyang Technological University, 2023)
LCL filter based current closed loop system and repetitive control system can reduce the static error of three-phase inverter. This paper presents a repetitive control system based on LCL filter current closed loop. According to the control characteristics of three-phase inverter, LCL filter is used, and its output is fed back to the current closed-loop system, and then the possibility of steady-state error of three-phase inverter is reduced by repeated control. The above assumption is modeled in this paper, and the model is simulated. It is confirmed that the system stability is greatly improved after the introduction of current closed-loop control based on LCL filter, according to the Bode diagram, and the system stability is also significantly improved after the overlapping and repeated control. The effectiveness of the proposed method and results is verified.